2020
DOI: 10.1007/s13365-020-00923-3
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencephalitis associated with COVID-19: a systematic review

Abstract: With the growing number of COVID-19 cases in recent times. significant set of patients with extra pulmonary symptoms has been reported worldwide. Here we venture out to summarize the clinical profile, investigations, and radiological findings among patients with SARS-CoV-2-associated meningoencephalitis in the form of a systemic review. This review was carried out based on the existing PRISMA (Preferred Report for Systematic Review and Meta analyses) consensus statement. The data for this review was collected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
1
20
0
4
Order By: Relevance
“…3,4 A growing body of evidence suggests that SARS-CoV-2 infection can affect the central nervous system (CNS), either directly or indirectly, and is associated with multiple neurological symptoms, from olfactory and gustatory dysfunction to more severe and uncommon events such as Guillain-Barré syndrome and encephalitis. [5][6][7][8][9] Great attention has also been dedicated to acute and chronic psychiatric symptoms associated with COVID-19. [10][11][12] In a prospective cohort study, anxiety, depression, and posttraumatic symptoms were observed in 23%, 18%, and 7%, respectively, of survivors of COVID-19 who had been hospitalized in an intensive care unit 4 months earlier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 A growing body of evidence suggests that SARS-CoV-2 infection can affect the central nervous system (CNS), either directly or indirectly, and is associated with multiple neurological symptoms, from olfactory and gustatory dysfunction to more severe and uncommon events such as Guillain-Barré syndrome and encephalitis. [5][6][7][8][9] Great attention has also been dedicated to acute and chronic psychiatric symptoms associated with COVID-19. [10][11][12] In a prospective cohort study, anxiety, depression, and posttraumatic symptoms were observed in 23%, 18%, and 7%, respectively, of survivors of COVID-19 who had been hospitalized in an intensive care unit 4 months earlier.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 A growing body of evidence suggests that SARS-CoV-2 infection can affect the central nervous system (CNS), either directly or indirectly, and is associated with multiple neurological symptoms, from olfactory and gustatory dysfunction to more severe and uncommon events such as Guillain-Barré syndrome and encephalitis. 5 , 6 , 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…As the pandemic progressed, review articles have been useful in combining available case reports and case studies 24 , 25 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 . These reviews were key to demonstrating prevalence of neurologic manifestations 46 among COVID-19 patients and to assess the prevalence of SARS CoV-2 presence in CSF as assessed by polymerase chain reaction (PCR) or serologic testing 47 .…”
Section: Case Reportsmentioning
confidence: 99%
“…The first case of encephalitis associated with SARS-CoV-2 infection was reported in May 2020 in a 24 year old man 57 and since then, many more cases have been identified. 58 Case studies have identified that the higher risk of neurological complications in patients with severe symptoms is caused primarily by a higher frequency of encephalopathy, especially in older patients. 14 , 23 Patients diagnosed with encephalitis have demonstrated signs of immune-mediated small-vessel damage, leading to altered integrity of the blood-brain barrier and brain edema.…”
Section: Introductionmentioning
confidence: 99%